نبدء عن مخطوطات الإباضية بشمال إفريقيا - النامي, عمرو خليفة (جمعية عمي سعيد, 1998)
Baḥḥāz 2003a, 194 note 2: Nubdha ʿan Makhṭūṭāt al-Ibāḍiyya bi-Shimāl Ifrīqiyā. A translation by ʿUmar b. Qāsim Mūsà Wāʿalī, with important additions. Printed by Jamʿiyyat ʿAmmī Saʿīd in Ghardaïa, 1998. A translation by Sulṭān b. Mubārak al-Shaybānī, 1970: Waṣf Makhṭūṭāt Ibāḍiyya muktashafa ḥadīthan fī Shimāl Ifrīqiyā. In Sahybānī 2008a, 214-248. For a Turkish translation, see Yıldız, Harun 2015d.
Keywords: Bibliothèques – Djebel Nefousa; Bibliothèques – Djerba; Manuscrits – Djebel Nefousa; Manuscrits – Djerba

Bibliothèques et manuscrits Abadites - Schacht, Joseph (Revue Africaine, 1956)
Schacht’s list is based on the catalogue of Makt. al-Quṭb and al-Makt. al-Ghannā’ in Beni Isguen (see p. 377 on these collections), and he did not list works already mentioned in GAL. Schacht mentions the following libraries: - Maktabat al-Quṭb in Beni Isguen, the library of the late Muḥ. b. Yūsuf Iṭfayyish. - Makt. al-Ghannā’, in the same house as the Makt. al-Quṭb. It is the library of the late Yaḥyà b. Muḥ. al-Ghanā’ī. Both these libraries are a Waqf. - The library of the late Ṣāliḥ b. ʿUmar al-Yasjanī in Beni Isguen. (In May 1972 I was told that no one is allowed entrance in this library. It is the second best library after the Makt. al-Quṭb). - The library of the late ʿAbd al-ʿAzīz al-Thamīnī in Beni Isguen. - The library of the late Saʿīd b. Yūsuf in Beni Isguen. (In May 1972 I was told that this library has been bought by Muḥ. b. Yūsuf Babānū). - The collection of Ibr. b. Bakīr. (He died in 1955 and his library has also been bought by Muḥ. b. Yūsuf Babānū). - The library of the late Yaḥyà b. Ṣāliḥ, Qāḍī of Melika, in Melika. (In May 1972 I was told that this is an important library. Its keeper was Ṣāliḥ ʿAbd al-Raḥmān). - The library of Muʿizz Aḥm. b. Yūsuf in Melika. (Member of the ʿAzzāba in May 1972). - The library of Aḥm. b. Ṣāliḥ in Melika. (Keeper in May 1972: Abū ‘l-Qāsim ʿAbd al-Ḥamīd, member of the ʿAzzāba. Called Maktabat Āl Skūtī). - The library of the late ʿUmar b. Ḥammū in El Ateuf. (In May 1972 this library was scattered). - The collection of Dāwud b. Yūsuf in El Ateuf. (In May 1972 I was given the name of Slimān b. Dāwud b. Yūsuf). - (In May 1972 I was given the name of Ayyūb b. Ibr. Jarrādī, in El Ateuf, as a possessor of Ibāḍī books). - The library of the late Bālḥājj [b. Kāsī] in Guerara. - The library of the late al-Shaykh al-Ṭarāblusī, a Waqf. (Was in the Masjid Berriane in May 1972). - The collection of ʿAbd al-Raḥmān al-Bakillī in Berriane. On page 376 note, Schacht mentions the following Ibāḍī libraries at Jerba: - The most important collection is al-Khizāna al-Bārūniyya [in al-Ḥashshān]. - Another important collection is the Khizānat al-Bāsī, in the mosque of al-Bāsī in Wālagh. This library was established in 1198/1783-4 by two brothers who traded with Istanbul, where they aquired many MSS. An old catalogue showed 225 vols., but Schacht found that all Ibāḍī works had disappeared, and that only about 100 non-Ibāḍī works remained. - The library of the Ibn Taʿrīt family has been scattered. - The larger part of the collection of the late Sul. al-Jāduwī in El-Adjim has been transferred to Hammam-Lif. - The collection of the late Ramaḍān al-Laynī was still in El-Adjim. - In Wālagh there are the Makt. al-Baʿtūr and the collection of ʿAmr b. Marzūq. - (The library of Sālim b. Yaʿqūb in Ghīzen should be added).
Keywords: Barrādī; Abū ‘l-Qāsim b. Ibrāhīm al-; Bibliothèques – Djerba; Bibliothèques – Mzab; Manuscrits – Djerba; Manuscrits – Mzab

Untersuchungen zu einigen ibaditischen Handschriften - Ess, Josef van (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 1976)
Descriptions, with many detailed annotations, of: - Jābir b. Zayd al-Azdī (d. between 93/711 and 104/722): Rasā’il. MSS in al-Khizānat al-Bāruniyya. (Ennami 1971, 65-66 (75?); Nachträge, 1-2). - Qatāda b. Diʿāma (d. 117/735 or 118/736): Aqwāl Qatāda. 7 parts. In Makt. Sālim b. Yaʿqūb. (Ennami 1971, 31 ff.; Nachträge, 2). (Ess 1986). - al-Rabīʿ b. Ḥabīb b. ʿAmr al-Farāhīdī: al-Musnad or al-Jāmiʿ al-Ṣahīḥ. (Nachträge, 2). - Abū Ghānim Bishr b. Ghānim al-Khurāsānī: al-Mudawwana. (Ennami 1971, 155 ff.; Nachträge, 2-3). - Hūd b. Muḥkim al-Hawwārī: Tafsīr. (Nachträge, 3). - Anonymous: Kitāb al-Jahālāt. (Nachträge, 3). - Abū Muḥ.: Kitāb al-Ḍiyā’. MS with Ṣāliḥ Bāʿimāra in Melika. - Anonymous: Dīwān al-Ashyākh. In al-Khizāna al-Bārūniyya, and two parts with Ṣāliḥ Bāʿimāra in Melika. - Abū Zak. Yaḥyà b. Abī Bakr al-Warjlānī (d. 471/1078): Kitāb al-Sīra wa-Akhbār al-A’imma. MS with Ṣāliḥ Bāʿimāra in Melika. (Nachträge, 3). - Tibghūrin (b. Bakr b. Jawād) b. ʿĪsà b. Dāwud al-Nafūsī al-Malshūṭī (d. circa 500/1106): Kitāb al-Uṣūl. With Ṣāliḥ Bāʿimāra in Melika. (Ennami 1971, II; Nachträge, 3). - Abū ʿAmr ʿUthmān b. Khalīfa al-Ṣūfī (1st half 6th/13th c.): Kitāb al-Su’ālāt. Incomplete MS with Ṣāliḥ Bāʿimāra in Melika. - Abū ʿAmmār ʿAbd al-Kāfī b. Abī Yaʿqūb b. Ism. al-Tanāwutī: Kitāb al-Mūjaz fī Taḥṣīl al-Su’āl wa-Takhlīṣ al-Ḍalāl. MS with Matharī (=Mutahhar) Ḥājj Muḥ. in Melika. - Abū ‘l-ʿAbbās Aḥm. b. Saʿīd al-Shammākhī (d. 928/1522): Mukhtaṣar Kitāb al-ʿAdl by Abū Yaʿqūb Yūsuf b. Ibr. al-Warjlānī. MS with Ṣāliḥ Bāʿimāra in Melika. (Ennami 1971, 292 ff.; Nachträge, 3-4). - Aḥm. b. Saʿīd al-Darjīnī (d. 2nd half 7th/13th century): Ṭabaqāt al-Mashāyikh. MS with Ṣāliḥ Bāʿimāra in Melika. - K. al-As’ila wa’l-Ajwiba li-Ahl ʿUmān. - Muḥ. b. Sul. b. Ṣāliḥ al-Mīzābī: Naẓm al-Nīl. (See Maghrib, Yasjanī, Abū ʿAbdl. Muḥ. b. Sul. b. Ṣāliḥ al-Mīzābī). - Muḥ. b. Yūsuf Iṭfayyish: commentary on Maʿālim al-Dīn of ʿAbd al-ʿAzīz al-Thamīnī. Autograph MS with Ṣāliḥ Bāʿimāra in Melika. - Muḥ. b. Yūsuf Iṭfayyish: commentary on the Lāmiyya of Ibn al-Naẓar. MS with Ṣāliḥ Bāʿimāra in Melika. (Nachträge, 4).
Keywords: Bibliographie; Bibliothèques – Mzab; Manuscrits – Djerba; Manuscrits – Mzab

A description of new Ibadi Manuscripts from North Africa - Nāmī, ʿAmr Khalīfa al- (Journal of Semitic Studies, 1970)
Baḥḥāz 2003a, 194 note 2: Nubdha ʿan Makhṭūṭāt al-Ibāḍiyya bi-Shimāl Ifrīqiyā. A translation by ʿUmar b. Qāsim Mūsà Wāʿalī, with important additions. Printed by Jamʿiyyat ʿAmmī Saʿīd in Ghardaïa, 1998. A translation by Sulṭān b. Mubārak al-Shaybānī, 1970: Waṣf Makhṭūṭāt Ibāḍiyya muktashafa ḥadīthan fī Shimāl Ifrīqiyā. In Sahybānī 2008a, 214-248. For a Turkish translation, see Yıldız, Harun 2015d.
Keywords: Bibliothèques – Djebel Nefousa; Bibliothèques – Djerba; Manuscrits – Djebel Nefousa; Manuscrits – Djerba